Analisis Manfaat Pembelajaran BIPA Melalui Selasar Bagi Mahasiswa Thailand di Universitas Muslim Nusantara Al-Washliyah: Pembelajaran BIPA Melalui Selasar - Sri Adinda; Sutikno Sutikno (Jurnal Komunitas Bahasa, 2025)
This study aims to analyze the benefits of Indonesian language learning for foreign speakers (BIPA) through the Selasar platform for international students at Universitas Muslim Nusantara Al-Washliyah. BIPA plays a vital role in facilitating the academic and social adaptation of international students in Indonesia. A descriptive qualitative approach was employed, with data collected through observations and questionnaires administered to BIPA participants. The findings indicate that the use of Selasar in BIPA learning provides several significant advantages, including improved access to learning materials, flexible learning schedules, and enhanced understanding of Indonesian culture. Moreover, the platform fosters interaction between students and instructors as well as among peers. However, certain challenges were identified, such as unstable internet connectivity and difficulties in adapting to the online learning environment. Overall, the results suggest that Selasar is an effective tool for supporting BIPA instruction, and further development of its content and features is recommended to optimize the learning experience for international students.